2016
DOI: 10.1111/jdi.12547
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diet on the efficacy of insulin lispro mix 25 and insulin lispro mix 50 as starter insulin in East Asian patients with type 2 diabetes: Subgroup analysis of the Comparison Between Low Mixed Insulin and Mid Mixed Insulin as Starter Insulin For Patients with Type 2 Diabetes Mellitus (CLASSIFY Study) randomized trial

Abstract: Aims/IntroductionThe pathophysiology of diabetes differs between Asian and Western patients in many ways, and diet is a primary contributor. The present study examined the effect of diet on the efficacy of 25% insulin lispro/75% insulin lispro protamine suspension (LM25) and 50% insulin lispro/50% insulin lispro protamine suspension (LM50) as starter insulin in Chinese and Japanese patients with type 2 diabetes and inadequate glycemic control with oral antidiabetic medication.Materials and MethodsThis was a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
3
1
1
Order By: Relevance
“…The results of this study suggested that Chinese T2DM patients should pay more attention to the selection of appropriate premixed insulin under the HCD pattern, which was helpful to reduce hypoglycemia episodes, especially nocturnal hypoglycemia. Chen et al, in the subgroup analysis of the CLASSIFY study, found no difference in nocturnal hypoglycemia between LM25 and LM50 under the HCD pattern (54% daily energy intake) [17], which was different from the results of our study. The reason may be that the HbA 1c level of the subjects in our study (mean 7.8%) was lower than that in the CLASSIFY study ([ 8.4%), and the risk of hypoglycemia was higher, so it may be easier to reflect the difference of drug characteristics in hypoglycemia.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study suggested that Chinese T2DM patients should pay more attention to the selection of appropriate premixed insulin under the HCD pattern, which was helpful to reduce hypoglycemia episodes, especially nocturnal hypoglycemia. Chen et al, in the subgroup analysis of the CLASSIFY study, found no difference in nocturnal hypoglycemia between LM25 and LM50 under the HCD pattern (54% daily energy intake) [17], which was different from the results of our study. The reason may be that the HbA 1c level of the subjects in our study (mean 7.8%) was lower than that in the CLASSIFY study ([ 8.4%), and the risk of hypoglycemia was higher, so it may be easier to reflect the difference of drug characteristics in hypoglycemia.…”
Section: Discussioncontrasting
confidence: 99%
“… 11 Traditionally, the Asian diet is high in carbohydrates, and so pre-mix insulins are a suitable choice as they target post-prandial hyperglycaemia. 25 However, newer insulin analogues can provide more stable glycaemic control and effective reduction of post-prandial hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“… 11 One of the main contributors could be the differences in diet, which is of particular importance, as a result of a higher glycemic response to carbohydrate consumption in Asian populations. 25 Other contributing factors in Asian populations include: differences in presentation of antiinsulin auto-antibodies in patients with T1D from Western compared with Asian populations, 1 , 26 a high proportion of patients who practice Ramadan (increased risk of hyper or hypoglycaemia) and a preference for pre-mix insulin. 11 Although some guidelines are available, there appears to be a difference between the guidelines and what HCPs do in practice in Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Las mezclas con un 50 % de insulinas de acción rápida reportan una mayor eficacia en pacientes con diabetes con alta ingesta de carbohidratos, de modo tal que las mezclas Mix50 podrían ser más apropiadas que las 25/30. Sin embargo, también es importante considerar los rasgos y preferencias de los pacientes 47 .…”
Section: Fundamentos De Elección Y Cálculo De Dosis De Insulinaunclassified